2017
DOI: 10.1108/aa-05-2016-046
|View full text |Cite
|
Sign up to set email alerts
|

Compliant assembly variation analysis of thin-walled structures based on the absolute nodal coordinate formulation

Abstract: Purpose Thin-walled structures inevitably always have manufacturing deviations, which affects the assembly quality of mechanical products. The assembly quality directly determines the performances, reliability and service life of the products. To achieve the automatic assembly of large-scale thin-walled structures, the sizing force of the structures with deviations should be calculated, and its assembling ability should be studied before assembly process. The purpose of this study is to establish a precise mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…To precisely describe the general typical bending and torsion deviations, a new ANCF irregular quadrilateral plate element (Yu et al , 2018) was proposed to discretize the thin-walled structures as shown in Figure A4. The coupling effect within the cross-sectional deformation could be settled using the high-order slope coordinates, which satisfies the requirement of deviation analysis for thin-walled structures.…”
Section: Force Equilibrium Equations Of System Via Absolute Nodal Coordinate Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…To precisely describe the general typical bending and torsion deviations, a new ANCF irregular quadrilateral plate element (Yu et al , 2018) was proposed to discretize the thin-walled structures as shown in Figure A4. The coupling effect within the cross-sectional deformation could be settled using the high-order slope coordinates, which satisfies the requirement of deviation analysis for thin-walled structures.…”
Section: Force Equilibrium Equations Of System Via Absolute Nodal Coordinate Formulationmentioning
confidence: 99%
“…The explicit expression of equation (7) is very complex. The detailed process can refer to (Yu et al , 2018). The GEFs Q A is a nonlinear function of nodal coordinates e and contains all the mechanical behavior of material.…”
Section: Force Equilibrium Equations Of System Via Absolute Nodal Coordinate Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al 42 proposed a nonlinear variation model (NVM) to consider the geometric nonlinearity, welding shrinkage, and angular distortion based on elastic mechanics. Yu et al 43,44 proposed a new irregular quadrilateral plate element based on the absolute nodal coordinate formulation (ANCF) to discretize the scalloped segment plates with shape deviations.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al. 23 used the shell element via the absolute nodal coordinate formulation to model the curved thin-walled structures, and the effects of the deviation forms, geometrical parameters and material properties on assembly quality of the thin-walled structures were investigated numerically.…”
Section: Introductionmentioning
confidence: 99%